Influence of Blast Furnace Slag on Concrete: Mechanical Strength and Microstructural Characterization - Yurihuaman, Edgar; Cordova, Gonzalo; Benavente, Christhian; Romero, Anjhinson (Civil Engineering Journal, 2025)
This study aims to quantitatively assess the effect of granulated blast furnace slag (GGBFS) as a partial replacement for Portland cement on the mechanical and microstructural performance of concrete with a design compressive strength of 280 kg/cm². A comprehensive experimental program was conducted to evaluate compressive strength, indirect tensile strength, flexural strength, and modulus of elasticity at curing ages of 7, 14, and 28 days, in accordance with ASTM standards. Microstructural characterization included Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy with Energy-Dispersive X-ray Spectroscopy (SEM/EDS), and X-ray Diffraction (XRD). The results demonstrated that incorporating GGBFS, particularly at 16% and 20% replacement levels, led to significant improvements in compressive strength and stiffness at 28 days, while early-age tensile strength reductions were mitigated over time due to the latent pozzolanic activity of the slag. Microstructural analyses revealed a denser cementitious matrix, enhanced chemical stability, and the formation of new crystalline phases. Statistical analyses (ANOVA and Kruskal–Wallis) confirmed significant effects on flexural strength and elastic modulus. These findings underscore the potential of GGBFS to improve concrete performance and promote sustainability by valorizing industrial by-products and reducing CO₂ emissions. This work provides a robust experimental and analytical basis for optimizing GGBFS incorporation in durable, performance-enhanced concretes.